The Effect of Taste Stimulation Program for Sodium Intake among High Risk of Hypertensive - Krainara, Kanjanaporn (Thammasat University Hospital Journal Online, 2022)
Background: Hypertension causes various complications resulting in disability and death. The best prevention is to encourage people to have appropriate health behaviors, where reducing sodium intake is an important factor that helps prevent new cases of hypertension. Objective: To study the effect of a taste stimulation program on sodium intake and blood pressure levels in hypertensive risk groups at Thung Yai District, Nakhon Si Thammarat Province. Material and methods: This Quasi-experimental research the experimental group received a 12 weeks taste stimulation program. The 1st week, we collected general information on how to cook and perception of salinity. The 2nd week, sodium intake was assessed as well as blood pressure measuring, educate/ practice cooking skills, reduce salt and taste stimulation. The 3rd week, self-management according to the manual for taste stimulation was performed. At the 11th-12th week, post-experimental data were collected. The control group was maintained according to the usual guidelines by providing health education and documents on risk reduction practices. Result: Results after 12 weeks of trial, the experimental group had mean sodium intake decreased from 2,984.38 (SD=515.63) to 1,718.75 (SD=309.46) mg./day. Mean systolic blood pressure decreased from 130.87 (SD=15.46) is 118.69 (SD=14.29) mmHg. And mean diastolic blood pressure decreased from 85.00 (SD=10.87) to 78.06 (SD=10.37) mmHg. which is statistically significant (p<.05). Conclusion: The research results were used as a guideline for people at high risk of hypertension to reduce their sodium intake which is resulted in a reduction of new cases of hypertension.